Description of Total Population Hospital Admissions for Treacher Collins Syndrome in Australia. (September 2022) - Junaid, Mohammed; Slack-Smith, Linda; Wong, Kingsley; Baynam, Gareth; Calache, Hanny; Hewitt, Timothy; Leonard, Helen
Objective: To describe patterns and demographic characteristics of total-population hospital admissions with a diagnosis of Treacher Collins syndrome (TCS) in Australia. Data Source: Population summary data for inpatient hospitals admissions (public and private) with a principal diagnosis of TCS (ICD10-AM-Q87.04) were obtained from the Australian Institute of Health and Welfare National Hospital Morbidity Database for a 11-year period (2002-2013). Main Outcome Measures: The primary outcome was hospital separation rate (HSR), calculated by dividing the number of hospital separations by estimated resident population per year. Trends in HSR s adjusted for age and sex were investigated by negative binomial regression presented as annual percent change and the association of rates with age and sex was expressed as incidence rate ratio. Results: In 244 admissions identified, we observed an increase of 4.55% (95% confidence interval [CI] −1.78, 11.29) in HSR's over the 11-year period. Rates were higher during infancy (1.87 [95% CI 1.42, 2.42]), declining markedly with increasing age. The average length of hospital stay was 6.09 days (95% CI 5.78, 6.40) per episode, but longer for females and infants. Conclusions: Findings indicate an increase in hospitalization rates, especially among infants and females which potentially relates to early airway intervention procedures possibly influenced by sex specific-disease severity and phenotypic variability of TCS. Awareness of the TCS phenotype and improved access to genetic testing may support more personalized and efficient care. Total-population administrative data offers a potential to better understand the health burden of rare craniofacial diseases.